Physical Training Risk Factors for Musculoskeletal Injury in Female Soldiers. Issue 12 (1st December 2014) - Roy, Tanja C.; Songer, Thomas; Ye, Feifei; LaPorte, Ronald; Grier, Tyson; Anderson, Morgan; Chervak, Michelle
ABSTRACT: Musculoskeletal injuries (MSIs) result in the most medical encounters, lost duty days, and permanent disability. Women are at greater risk of injury than men and physical training is the leading cause of injury. The purpose of this study was to investigate the demographic, body composition, fitness, and physical training risk factors for injuries in female Soldiers serving in garrison Army units over the past 12 months. Self-report survey was collected from 625 women. The ankle was the most frequently injured body region, 13%. Running was the activity most often associated with injury, 34%. In univariate analysis lower rank, older age, history of deployment, no unit runs, weekly frequency of personal resistance training, and history of injury were all associated with injury. In multivariate analysis rank, history of injury, weekly frequency of unit runs, and weekly frequency of personal resistance training were the best combination of predictors of injury. Running once or twice a week with the unit protected against MSIs, whereas participating in personal resistance training sessions once or twice a week increased the risk of MSIs. With more emphasis on running and resistance training, the U.S. Army could reduce injuries and save billions of dollars in training and health care costs.